DEVELOPMENT OF PROJECT-BASED LEARNING-BASED STUDENT WORKSHEETS ONSIMPLE DISTILLATION MAT ERI AT SMPN / MTSN TANAH PINOH - Desy Ramadhani Putri; Rahmat Rasmawan; Maria Ulfah; Hairida Ulfah; Rini Muharini (Sean Institute, 2023)
This study aims to determine the feasibility and response of teachers to project-based learning (PjbL) student work performance (LKPD) on mixed separation material. This research is research and development or R & D (research and development). The development model used is model ADDIE which is adapted into 3 stages, namely analysis (analyze), design (d esign), and development (development). The subject of this study is project-based learning (PjbL) based student work (LKPD). The test subjects in this study involved 6 science teachers, 3 MTSN 1 Tanah Pinoh science teachers, 2 science teachers from SMP IT Imam Syafi'i and 1 science teacher from SMPN 4 Tanah Pinoh. Data collection techniques are carried out through measurement techniques and indirect communication techniques, with assessment instruments, validation questionnaires and response test questionnaires. The feasibility of PJBL-based LKPD is assessed in material, media and language aspects carried out by three experts in each field. Material eligibility was obtained on average 94.7% with the